Enabling Knowledge Flow: Retaining Graduate Women in the Singapore Construction Industry - Yean , Florence Yng Ling; Leow, Lena (Penerbit Universiti Sains Malaysia, 2008)
As extensive resources are expanded in transferring knowledge from universities to undergraduates, it is important for them to enter the workforce upon graduation to enable the knowledge to flow to the industry. The aim of this study is to investigate the extent to which knowledge flow is disrupted because graduate women are not entering the Singapore construction industry to ensure its sustainable growth. This study used a structured questionnaire, with data collected from 116 construction-trained graduate women via postal survey. Results show that 58% of them chose not to enter or are considering leaving the construction industry. The disruption in knowledge flow is due to better prospects in other industries (pull factor) and poor job conditions within the construction industry (push factor). To retain graduate women in the construction industry, it is recommended that employers: introduce flexible work schedule; allow graduate women to work from home; and give them the same opportunities as their male counterparts